Perkecambahan Benih Padi (Oryza sativa L.) Lokal Asal Kalimantan Barat Berdasarkan Tingkat Salinitas - Riza Linda, Yessy Melda Halindra, Elvi Rusmiyanto Pancaning Wardoyo, (Universitas Tanjungpura, 2017)
The selection of variety of local rice from West Kalimantan is essential in order to increase the production of reice seed. Rice seed that is resistant to saline concentration is especially needed to increase production. The purpose of this research is to know the effect of salinity on the seed germination of local rice varieties from West Kalimantan. This research used rolled paper test technique with standing position, and the research design used was Completely Randomized Design (CRD) with NaCl treatment at 0 ppm (control), 2000, 4000, 6000, and 8000 ppm with 5 repetitions. The rice varieties that were used were Padi Putri, Padi Renggak, Padi Bungkok, Padi Gadis, Padi Waes, Padi Banjar, Padi Beras merah, Padi Kunyit and Padi Ketan. The research findings showed the presence of salinity-level effect on the growth of local rice seed germination. The nine varieties of local rice from West Kalimantan could survive in condition with NaCl solution concentration at the range of 2000 – 8000 ppm.